Acute effect of a fight of Mixed Martial Arts (MMA) on the serum concentrations of testosterone, cortisol, creatine kinase, lactate, and glucose - Rodrigo Poderoso de Souza; Maria do Socorro Cirilo de Sousa; Eduardo Borba Neves; Claudio Rosa; Igor Raineh Durães Cruz; Adenilson Targino Júnior; José Onaldo Ribeiro Macedo; Victor Machado Reis; José Vilaça-Alves (Desafio Singular, 2017)
The aim of this study was to analyse the serum concentrations of testosterone (T), cortisol (C), lactate (LAC), creatine kinase (CK) and glucose (GLU) on mixed martial arts (MMA) athletes, before and after a fight. We divided 20 MMA athletes into two groups of 10 fighters each, according to the result of a fight, and were then evaluated four times: 24 hours before (-24h), one hour before (-1h), immediately after (0h) and 24 hours after the fight (+24h). It was observed: a significant decrease in T and T/C between moment -24h and 0h and a subsequent increase between the moment 0h and +24h and a reverse behaviour in variables C, LAC and GLU (p<0.0001); a decrease in CK between moment -24h and -1h and an increase between moment -1h and +24h (p<0.0001); and differences between winners and losers T levels, in moments -24h, -1h, 0h and +24h (p = 0.009 e p < 0.001, p = 0.005 e p = 0,001, T and C, respectively), in T/C in the moments -24h and 0h (p=0.006 and p=0.001, respectively) and in GLU levels (p<0.0001) in the moment 0h. Therefore, it seems that an MMA fight leads to metabolic stress and muscle damage, regardless of the result of the fight. The coaches have now more biochemical and hormonal references and indicators in response to an MMA fight.